Accounting in a Business Context - Berry, Aidan; Jarvis, Robin, 1946- (2011)
The primary focus is on how managers use information in the real world, rather than how accountants prepare it. Students learn the role of accounting in its wider managerial setting, without needing to know unnecessary technical detail or jargon.
Previous edition: London: Thomson Learning, 2007.
Includes index.
Keywords: Accounting; Finance and Accounting